2004
DOI: 10.1023/b:phar.0000026807.59766.ae
|View full text |Cite
|
Sign up to set email alerts
|

Continuing education and community pharmacists in Galicia: a study of opinions

Abstract: Community pharmacists in Galicia show a great interest in the provision and organization of continuing education activities that meet their needs and expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 3 publications
2
13
0
1
Order By: Relevance
“…In a similar study done in community pharmacy in the UAE, pharmacists also wanted to see programs offering innovations in pharmacy practice and in disease management and to a lesser extent literature evaluation skills and certificate programs [17]. Other studies have also showed pharmacists are in general acceptance of pharmaceutical care concept and want educational programs that will skill them to do it [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study done in community pharmacy in the UAE, pharmacists also wanted to see programs offering innovations in pharmacy practice and in disease management and to a lesser extent literature evaluation skills and certificate programs [17]. Other studies have also showed pharmacists are in general acceptance of pharmaceutical care concept and want educational programs that will skill them to do it [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that the difficulties that the elderly experience during the process of adherence to their pharmacotherapy were not fully explored. Furthermore, there is a gap in the knowledge available with regard to pharmacist interventions used to inform these users about their therapy 5,18…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we observe that the involvement of the pharmacy professional in the conduction of programs for the rational use of drugs by the geriatric population is indispensable 17,18…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that individual professionals may not always be clearly aware of their learning needs, their knowledge gaps and practice deficiencies 1 . However, individuals' perceptions of specific conditions, opportunities and needs may motivate them to participate in continuing education 8,9 .…”
Section: Discussionmentioning
confidence: 99%